2011
DOI: 10.1007/s10815-011-9680-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of embryo transfer quality on pregnancy and live birth delivery rates

Abstract: Background To analyze the effects of embryo transfer (ET) quality on clinical pregnancy (CPR) and live birth delivery rates (LBDR). Methods In a retrospective study at a single, private infertility center between November 2005 and December 2009 one thousand fifty-five day-3 and day-5 ETs following IVF/ICSI/IMSI were evaluated. We analyzed the impact of an atraumatic ET with a soft catheter (ET 1), after external guidance (ET 2), after probing of the cervix with a stylet (ET 3), or after grasping the portio vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The observation that presence of blood on the catheter is associated with poor outcome has been also showed by numerable previous studies (2,7,8,14,15,16) . More specifically, the presence of blood on the tip of the catheter, rather than on the outer sheath was shown to be associated with poor outcome (8) .…”
Section: Discussionsupporting
confidence: 52%
“…The observation that presence of blood on the catheter is associated with poor outcome has been also showed by numerable previous studies (2,7,8,14,15,16) . More specifically, the presence of blood on the tip of the catheter, rather than on the outer sheath was shown to be associated with poor outcome (8) .…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, either 40 μl hCG dissolved in embryo culture medium or 40 μl plain culture medium was applied to the surface of the endometrium using a Wallace embryo replacement catheter (Smiths Medical Inaternation, Kent, UK) 0.5 cm below the uterine fundus. Transfer of blastocysts was performed as described previously [ 26 ]. No statistically significant differences in patient characteristics between hCG and control groups were observed (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…• Degree of difficulty of the procedure (Lesny et al, 1998;Sallam & Sadek, 2003;Spitzer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported better pregnancy rates when using more flexible catheters, despite an association with increased ET procedure difficulty (Abou-Setta et al, 2005;Kably Ambe et al, 2011;Mansour et al, 1990;Saldeen et al, 2008;Spitzer et al, 2012;Wood et al, 1985). We have been using semi-rigid Frydman® Classic 4.5 catheters (CCD Laboratoire, Paris, France) for over ten years in our ET procedures.…”
Section: Introductionmentioning
confidence: 99%